2014
DOI: 10.1111/agec.12117
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity in Mexico: the effect of international migration

Abstract: This article estimates the effect of international migration from Mexico to the United States on the obesity status of children who remain in Mexico. Theory suggests that increased liquidity as well as changing time allocations resulting from migration may influence obesity outcomes. Natural disasters are used as an identification strategy. Results suggest that older boys in urban areas are more likely to become obese when either a male or female migrates from the household, while girls in urban areas are less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…On the other hand, migration also significantly increases the consumption of fruit and vegetables by approximately 35 per cent. These results support earlier findings on changes of dietary habits of MSHs: remittances in Ecuador do not translate to long‐term nutritional effects (Anton, ), children who stay behind experience poorer diet quality in Tonga (Gibson et al ., ), migration has shifted household consumption to less nutritious food in Ghana (Karamba et al ., ), and international migration from Mexico increases the probability of childhood obesity among older boys (Damon & Kristiansen, ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, migration also significantly increases the consumption of fruit and vegetables by approximately 35 per cent. These results support earlier findings on changes of dietary habits of MSHs: remittances in Ecuador do not translate to long‐term nutritional effects (Anton, ), children who stay behind experience poorer diet quality in Tonga (Gibson et al ., ), migration has shifted household consumption to less nutritious food in Ghana (Karamba et al ., ), and international migration from Mexico increases the probability of childhood obesity among older boys (Damon & Kristiansen, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has confirmed this problem when they saw that migrants household often make wrong food choices, shifting towards the consumption of potentially less nutritious food, mostly starch and sugary food (Karamba et al 2011). Consistency in this way of feeding may lead to child obesity (Damon and Kristiansen 2014;Howard and Stanley 2017). Hence, the policy that encourages dietary choice education in high migrant communities is necessary for improving the nutritional level of migrant households.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…requirements, but at the same time reduces the number of family labour available for food production (Maharjan et al 2013;Urama et al 2017). The second subset of studies examines the potential of the household to receive remittances and information which could directly increase the expenditure and consumption of nutritious food (Damon and Kristiansen 2014;Isoto and Kraybill 2017;Karamba et al 2011). The third subset shows the possibilities of remittances and information to indirectly improve food security by enabling the household to invest in food production and other non-agricultural activities (Atamanov and Van den Berg 2012;Böhme 2015;McCarthy et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…3,42 The most recent self-reported data show that 3-to 12-year-old children spend between 1.6 and 2.9 hours per day in front of a screen, 27,43,44 while adolescents older than 12 years spend between 7.5 and 14.4 hours per week in front of a screen. 45 A study from Mexico City shows that 7-year-old children (n = 173) watch, on average, between 4.9 and 5.3 television programs per day. 34 Overall, girls exhibit higher levels of sedentary behavior than boys 33,34,46 and accelerometry data show that girls spend 73.4% of their awake time in sedentary activities.…”
Section: Sedentary Behavior: D (4)mentioning
confidence: 99%